Genomic Characterization of CIAV Detected in Contaminated Attenuated NDV Vaccine: Epidemiological Evidence of Source and Vertical Transmission From SPF Chicken Embryos in China - Li, Yan; Wang, Jinjin; Chen, Longfei; Wang, Qun; Zhou, Meng; Zhao, Hui; Chi, Zengna; Wang, Yixin; Chang, Shuang; Zhao, Peng (Frontiers in Veterinary Science, 2022)
Live attenuated vaccines have been extensively used to prevent infectious disease in poultry flocks. Freedom from exogenous virus is a high priority for any veterinary vaccines. Recently, attenuated Newcastle disease virus (NDV) vaccines were detected to be contaminated with chicken infectious anemia virus (CIAV) in a routine screening for exogenous viruses. To investigate the possible source of the contamination, we conducted virological tests on a specific-pathogen-free (SPF) layer breeder flock that provide the raw materials for vaccines in this manufacturer. Firstly, CIAV antibodies in serum and egg yolks samples of the SPF laying hens were detected by ELISA assays. The results showed that CIAV antibodies in serum and egg yolks were 62% positive and 57% positive, respectively. Then, DNA was extracted from the NDV vaccines and SPF chicken embryonated eggs, and detected by molecular virology assays. The results showed that three assays for pathogens in embryonated eggs had similar positive rates (35.8%). And the sequences of CIAV from SPF embryos and NDV vaccines consisted of 2,298 nucleotides (nt) with 100% homology. The new full-length genome of CIAV was designated SDSPF2020 (Genbank accession number: MW660821). Data showed SDSPF2020 had the sequence similarities of 95.8–99.6% with reference strains, and shared the highest homology with the Chinese strain HLJ15125. These results strongly suggested that exogenous CIAV contamination is most likely caused by wild virus infection in SPF flocks and vertical transmission to chicken embryos. Collectively, this study illustrated that vertical transmission of CIAV from a SPF layer breeder flock to embryos was a non-neglible way for exogenous virus contamination in vaccine production.